2014
DOI: 10.1002/ase.1453
|View full text |Cite
|
Sign up to set email alerts
|

Spatial abilities of medical graduates and choice of residency programs

Abstract: Spatial abilities have been related in previous studies to three-dimensional (3D) anatomy knowledge and the performance in technical skills. The objective of this study was to relate spatial abilities to residency programs with different levels of content of 3D anatomy knowledge and technical skills. The hypothesis was that the choice of residency program is related to spatial abilities. A cohort of 210 medical graduates was enrolled in a prospective study in a 5-year experiment. Spatial abilities were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 73 publications
5
21
0
Order By: Relevance
“…They required participants to use some forms of mental rotation processing, and/or to spatially manipulate and transform representations of the 3D scapula structure. This is consistent with previous studies (e.g., Rochford, 1985;Garg et al, 2001Garg et al, , 2002Guillot et al, 2007;Langlois et al, 2015) that have underlined the MRT as a good predictor of success in learning anatomy.…”
Section: Does Learning Functional Anatomy Of a Structure And Its Assosupporting
confidence: 93%
See 1 more Smart Citation
“…They required participants to use some forms of mental rotation processing, and/or to spatially manipulate and transform representations of the 3D scapula structure. This is consistent with previous studies (e.g., Rochford, 1985;Garg et al, 2001Garg et al, , 2002Guillot et al, 2007;Langlois et al, 2015) that have underlined the MRT as a good predictor of success in learning anatomy.…”
Section: Does Learning Functional Anatomy Of a Structure And Its Assosupporting
confidence: 93%
“…In the former case, the interplay between the MRT scores and presentation formats sheds light on the role of the spatial relation ability during the visualization processing. In the latter case, the predicting role of the MRT scores for successful anatomy performance replicated evidence provided by numerous studies relevant to the literature in the anatomy domain (e.g., Rochford, 1985;Garg et al, 2001Garg et al, , 2002Guillot et al, 2007;Langlois et al, 2015).…”
Section: Does Learning Functional Anatomy Of a Structure And Its Assosupporting
confidence: 66%
“…This study demonstrated that a high-resolution 3D digital platform with a full-size, virtual liver and gallbladder is an appropriate resource for teaching anatomy in Medicine. This statement -supported by other studies in the literature 14,15 -is supported by the fact that the virtual anatomical table was able to provide the information to the medical student as well as a formalin-preserved real liver. This finding is demonstrated because both groups increased their knowledge from the baseline.…”
Section: Discussionsupporting
confidence: 63%
“…In particular, the introduction of cone‐beam computerized tomography in practice has increased the need for the development of pedagogical elements dealing with the 3D representation and interpretation of anatomical and dental structures. Anatomy textbooks and atlases provide limited benefit with regards to 3D visualization of structures as they present static 2D images (Langlois et al, ). The visual‐spatial ability to mentally manipulate a 3D structure and recognize its features is becoming increasingly important as time with appropriate anatomical models is reduced and reliance on 2D images is increased (Azer and Azer, ).…”
Section: Discussionmentioning
confidence: 99%